Generation of the Bovine Viral Diarrhea Virus E0 Protein in Transgenic Astragalus and Its Immunogenicity in Sika Deer. (22nd May 2014) - Gao, Yugang; Zhao, Xueliang; Zang, Pu; Liu, Qun; Wei, Gongqing; Zhang, Lianxue
Abstract : The bovine viral diarrhea virus (BVDV), a single-stranded RNA virus, can cause fatal diarrhea syndrome, respiratory problems, and reproductive disorders in herds. Over the past few years, it has become clear that the BVDV infection rates are increasing and it is likely that an effective vaccine for BVDV will be needed. In this study, transgenic Astragalus was used as an alternative productive platform for the expression of glycoprotein E0. The immunogenicity of glycoprotein E0 expressed in transgenic Astragalus was detected in deer. The presence of pBI121-E0 was confirmed by polymerase chain reaction (PCR), transcription was verified by reverse transcription- (RT-) PCR, and recombinant protein expression was confirmed by ELISA and Western blot analyses. Deer that were immunized subcutaneously with the transgenic plant vaccine developed specific humoral and cell-mediated immune responses against BVDV. This study provides a new method for a protein with weak immunogenicity to be used as part of a transgenic plant vaccine.